Pengaruh Rendaman Air Laut Pasang Surut terhadap Campuran Lapis Aspal Beton AC-WC dengan Modifikasi Steel slag Ramah Lingkungan - Emil Adly (Bulletin of Civil Engineering, 2021)
Road pavement near coastal area has greater chance for seawater immersion. Along the road of Pantai Utara especially on Jalan Kaligawe Raya, Semarang, Jawa Tengah, tidal seawater flood often occurs. Road pavement that is immersed by water is potentially damaged since water is one of the causing factors of damage in road pavement. Recurring weight also will decrease the design life and the road degrades faster. The buildup of unused waste from steel factory can be an alternative material for modified asphalt mix. The test result of 6, 12, and 24 hours seawater immersion indicated poor marshall characteristic value marked by the decrease of density value, VFA (Void Filled Asphalt), stability, and MQ (Marshall Quotient), and indicated the increase in VIM (Void In the Mix), VMA (Void in Mineral Aggregate), and flow.